True blood : investigating vampires and Southern Gothic - Cherry, Brigid, 1957- (Investigating cult TV., 2012)
As seen in HBO's True Blood , vampires have never been more edgy, gory or sexy. Since its arrival on screen in 2008, Alan Ball's adaptation of The Southern Vampire Mysteries by Charlaine Harris has exploited the creative freedoms of the HBO brand and captured a cult audience with its passionate, blood-drenched visuals and stories. From viral webisodes depicting vampires announcing themselves on TV to the steamy title sequence and the show's uninhibited use of language, sex and gore, True Blood has quickly gained status as cult TV with bite. True Blood posed the question of what would happen if vampires 'came out of the coffin' and this book considers the representations of sexuality, race and class in a series that engages directly with prejudice and civil rights. It also considers True Blood's generic roots in television horror, paranormal romance and Southern Gothic, the wider contexts of fairy tales and religion, the marketing of the series and the activities of its fans. Written for students, scholars and fans, True Blood: Investigating Vampires and Southern Gothic explores the hidden depths of True Blood's vampire bars, small town communities and haunted bayous.